Strategi Pengelolaan Media Sosial Instagram @pertamina.corpu Sebagai Sarana Branding - Prameswari, Annabel Natasha (Prisani Cendekia Institute, 2025)
With the advancement of technology today, many people are utilizing it to carry out daily activities more easily and efficiently. As a result, social media has become increasingly popular as a platform that provides both information and entertainment. Amid the rapid development of digital media, social media has emerged as a crucial tool for communication and branding activities, including within corporate environments such as Pertamina Corporate University.This research aims to examine the management strategy of the Instagram account @pertamina.corpu in building its image and strengthening its branding as Pertamina's corporate university. The study also seeks to provide insights into effective Instagram social media management strategies by applying the SOSTAC method, supported by Cutlip and Center’s communication theory. This study employs a qualitative descriptive method. Data collection techniques include interviews, observation, and documentation. The analysis follows the descriptive approach using the data analysis model developed by Miles and Huberman, which involves data collection, data reduction, data display, and conclusion drawing. Overall, this social media management strategy has contributed to building brand awareness and strengthening the institutional image of Pertamina Corporate University through digital platforms.